Advances in metallic ion-doped hydroxyapatite: unlocking enhanced structural, biological, and functional properties for cutting-edge biomedical applications - Kareem, Rebaz Obaid; Barzinjy, Azeez A.; Ates, Tankut; Bulut, Niyazi; Keser, Serhat; Kaygili, Omer (Springer, 2026)
Hydroxyapatite (HAp) is a biomaterial that has been extensively studied for its exceptional biocompatibility, osteoconductivity and non-toxic nature, making it highly suitable for applications in bone and dental tissue engineering. This review evaluates the incorporation of metallic ions into the HAp lattice as a strategic approach to optimize its structural integrity, mechanical performance and biological functionality. Quantitative findings from recent studies show that Ag+ doping at 1 wt% reduces bacterial growth by over 95%, but higher doses ( > 3 wt%) can reduce cell viability by up to 20%. Sr2 + (5 wt%) improves bone regeneration by 25%, though excessive levels may alter lattice stability. Zn2 + at 3 wt% enhances osteoblast proliferation by 60% but can slightly reduce thermal stability. Cu2 + improves angiogenesis and antimicrobial efficacy, but high concentrations can induce cytotoxicity. Furthermore, metallic ion doping enhances the dielectric properties and contributes to anti-cancer capabilities, expanding HAp's therapeutic potential. The review also highlights advanced applications of metallic ion-doped HAp, including its role in drug delivery systems, implant surface coatings, and even environmental remediation. By synthesizing findings from recent studies, this comprehensive analysis underscores the transformative impact of metallic doping in optimizing HAp for diverse biomedical applications. These advances represent an important step in the development of multifunctional biomaterials, paving the way for innovative solutions to medical and environmental challenges.
Keywords: Hydroxyapatite; Metal ion-doped; Biomedical applications; Biocompatibility; Drug delivery